2020
DOI: 10.1111/1750-3841.15443
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial strategies for production improvement of red pigments from Antarctic fungus Geomyces sp. 

Abstract: Natural red pigments have been widely used as food and cosmetics additives. However, due to toxic byproducts or allergen issues, it is still necessary to look for some other red pigment products. This study proposed combinatorial strategies to improve production of a new kind of red pigments from the fungus Geomyces WNF-15A, isolated from Antarctica. A high-production medium was developed by statistical experimental design, which was further simplified for industrial use by single-factor experiments. Strain br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Our previous studies have shown that atmospheric and room temperature plasma (ARTP) is highly lethal to Geomyces sp. WNF-15A, with a fatality rate of up to 90% (Huang et al, 2020 ). We obtained a dominant mutant M210 using ARTP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies have shown that atmospheric and room temperature plasma (ARTP) is highly lethal to Geomyces sp. WNF-15A, with a fatality rate of up to 90% (Huang et al, 2020 ). We obtained a dominant mutant M210 using ARTP.…”
Section: Resultsmentioning
confidence: 99%
“…For shake flask culture, the second-order seed was inoculated in 75 mL medium S by 6% (vol/vol), and 20 glass beads with a diameter of 4 mm were added. It was then cultured in dark at 130 r/min for 16 days (Huang et al, 2020 ). Three biological replicates were set for each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The seed medium and fermentation medium S for Geomyces sp. WNF-15A and its mutants were used as previously described (Huang et al, 2020).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%